Effect of Helichrysum Oil on Toothache - Kamalli.M; Gayatri Devi R; Jothi Priya.A; Saravana Kumar.S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Toothache is the pain or inflammation in the tooth. A symptom of toothache includessensitivity, gum bleeding, cavities etc. Toothache can occur due to improper an dental care and oral hygienepractice which is one of the commonest reasons. The genus Helichrysum consists of about 600 specieswhich are flowering in the family of sunflower. The other names are Italian strawflower and Immortelle.It grows on dry, rocky and sandy regions in the Mediterranean. It has anti-inflammatory, antispasmodicand analgesic properties. The aim of the study is to determine the effect of helichrysum oil on toothache.Materials and Methods: The sample size of the study was 15 individuals with toothache who visited thedental clinics. Participants having periodontal problems, cardiovascular problems were excluded from thestudy. To every 2 drops of helichrysum oil, 1 ml of coconut oil was added. The intensity of the pain wasmeasured by using the pain scale. The participants were given to apply it on the gingival area of the painfultooth. The patients were followed to know the intensity of pain after a few hours. The results were tabulatedand then statistically analysed. Results and Discussion: 27% of the participants have moderate pain after afew hours of application of oil. 26% of them have less pain. 13% of participants have very little pain. 27%of them do not feel any change in the intensity of pain. 7% have high pain. Conclusion: From this studyit was evident that helichrysum oil had an effect in reducing the tooth ache as helichrysum possess antiinflammatoryproperties.